2005
DOI: 10.1111/j.1399-6576.2005.00837.x
|View full text |Cite
|
Sign up to set email alerts
|

High success rate and low incidence of headache and neurological symptoms with two spinal needle designs in children*

Abstract: Both needles were associated with a high success rate and a low incidence of complaints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 19 publications
(39 reference statements)
3
35
1
2
Order By: Relevance
“…Of the 25 RCTs, 15 [5,14,21,2325,27–31,38–41] reported the severity of PDPH which could be graded as mild or severe. These 15 studies enrolled 3570 patients, with 1854 patients in cutting spine needle group and 1716 patients in pencil-point spine needle group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 25 RCTs, 15 [5,14,21,2325,27–31,38–41] reported the severity of PDPH which could be graded as mild or severe. These 15 studies enrolled 3570 patients, with 1854 patients in cutting spine needle group and 1716 patients in pencil-point spine needle group.…”
Section: Resultsmentioning
confidence: 99%
“…The robustness of the result was tested by excluding these 4 studies, and no obvious change happened. Third, of all the studies, 14 [5,14,21,22,24,25,27,28,31,32,36,37,40,42] were performed in Europe, 6 [23,26,29,30,34,39] in North America, 4 [33,35,38,41] in Asia, and 1 [20] in Africa, reflecting a limitation of the evidence generalization. Lastly, all the documents were in English, meaning the possibility of language bias.…”
Section: Discussionmentioning
confidence: 99%
“…However, these data are confounded because spinal anaesthesia is usually performed by doctors with more experience than many of the doctors doing diagnostic LPs. Four randomised trials in children having spinal anaesthesia with 24-gauge or smaller needles found little evidence of a difference in the rate of LP headache between different needle sizes and needle designs 10 12 14 15. The benefit, if any, of using 25-gauge needles for LPs compared with the standard 22-gauge needle therefore remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Çocuk-larda spinal iğne tercihinde keskin uçlu ve kalem uçlu iğnelerin benzer başarı oranları olduğunu belirten yayınlar mevcuttur. [7][8][9] Apilioğulları ve ark.nın 414 pediatrik hastada yapmış oldukları ça-lışmada, baş ağrısı oranı keskin uçlu iğnelerle %4,5, kalem uçlu iğnelerle ise %0,4 olarak belirtilmiştir. 10 Çalışmamızda 26 G keskin uçlu iğne kullanılmış ve hastalarımızın hiçbirinde baş ağrısı tespit edilmemiştir.…”
Section: Discussionunclassified